Prevalence of Autism Spectrum Disorder in the Centro region of Portugal: a population based study of school age children within the ASDEU project - Rasga, Célia; Santos, João Xavier; Café, Cátia; Oliveira, Alexandra; Duque, Frederico; Posada, Manuel; Nunes, Ana; Oliveira, Guiomar; Vicente, Astrid Moura (Frontiers in Psychiatry, 2023)
Accurate prevalence estimates for Autism Spectrum Disorder (ASD) are fundamental to adequately program medical and educational resources for children. However, estimates vary globally and across Europe, and it is therefore wise to conduct epidemiological studies in defined geo-cultural contexts. In this study, we estimated the prevalence of ASD in the Centro Region of Portugal, as part of the Autism Spectrum Disorder in the European Union (ASDEU) project. The overall prevalence was 0.5% (95% CI 0.3-0.7), higher in schools with Autism Units (3.3%, 95%CI 2.7-3.9) than in regular schools or schools with Multiple Disability Units (0.3%, 95% CI 0.1-0.5 and 95% CI 0.04-0.6, respectively). This indicates that the diagnosis of autism is followed by the most effective educational policies. The prevalence estimates variability across the different regions from the ASDEU project is discussed.